2011
DOI: 10.1063/1.3565018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of current sheet formation in a quasiseparatrix layer using adaptive mesh refinement

Abstract: The formation of a thin current sheet in a magnetic quasiseparatrix layer ͑QSL͒ is investigated by means of numerical simulation using a simplified ideal, low-␤, MHD model. The initial configuration and driving boundary conditions are relevant to phenomena observed in the solar corona and were studied earlier by Aulanier et al. ͓Astron. Astrophys. 444, 961 ͑2005͔͒. In extension to that work, we use the technique of adaptive mesh refinement ͑AMR͒ to significantly enhance the local spatial resolution of the curr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…In contrast, QSLs, quantified by the squashing factor Q ≫1 (Titov et al 2002), are thin volumes where the connectivity of field lines changes drastically but still continuously (Priest & Démoulin 1995;Demoulin et al 1997). Due to the strong distortion of magnetic mapping at QSLs, the generic buildup of intense electric current sheets along QSLs is expected analytically (Demoulin et al 1996), and confirmed later on by numerical simulations (e.g., Aulanier et al 2005;Effenberger et al 2011;Craig & Effenberger 2014). In the case of QSLs, the continuous exchange of connectivity between neighboring field lines induces an apparent "slipping" motion of field lines, which is termed "slipping reconnection" if the speed is sub-Alfvénic, or "slip-running reconnection" if the speed is super-Alfvénic (Aulanier et al 2006).…”
Section: Introductionmentioning
confidence: 80%
“…In contrast, QSLs, quantified by the squashing factor Q ≫1 (Titov et al 2002), are thin volumes where the connectivity of field lines changes drastically but still continuously (Priest & Démoulin 1995;Demoulin et al 1997). Due to the strong distortion of magnetic mapping at QSLs, the generic buildup of intense electric current sheets along QSLs is expected analytically (Demoulin et al 1996), and confirmed later on by numerical simulations (e.g., Aulanier et al 2005;Effenberger et al 2011;Craig & Effenberger 2014). In the case of QSLs, the continuous exchange of connectivity between neighboring field lines induces an apparent "slipping" motion of field lines, which is termed "slipping reconnection" if the speed is sub-Alfvénic, or "slip-running reconnection" if the speed is super-Alfvénic (Aulanier et al 2006).…”
Section: Introductionmentioning
confidence: 80%
“…While QSLs do not have a discontinuous mapping, the magnetic field line connectivity changes strongly, such that similar current sheets can be expected (Démoulin, Henoux, et al, ). Indeed, current accumulation at QSLs has been demonstrated in MHD simulations (Aulanier et al, ; De Moortel & Galsgaard, ; Effenberger et al, ) and observations (Janvier et al, ).…”
Section: Alfvén Waves and Magnetic Topologymentioning
confidence: 91%
“…They demonstrate a complex QSL/HFT structure associated with the present magnetic configuration, which has more structures than a "mere" X-shaped crossing. Since the HFT corresponds to the high-Q region, and since intense currents build up where field lines anchored very close to each other have opposite feet widely separated (Démoulin et al 1996a), one can expect the formation of a high-current region around the HFT, such as found in Aulanier et al (2005b) and Effenberger et al (2011) in non-eruptive models. Similar results are obtained here, as shown with the zoom of the current layer on the right panel of Fig.…”
Section: Coronal Magnetic Topology and Electric Currentsmentioning
confidence: 99%